(untitled) (Washington, 2003)
In Living with the Genie, leading writers and thinkers come together to confront this question from many perspectives, including: Richard Powers's whimsical investigation of the limits of artificial intelligence; Philip Kitcher's confrontation of the moral implications of science; Richard Rhodes's exploration of the role of technology in reducing violence; Shiv Visvanathan's analysis of technology's genocidal potential; Lori Andrews's insights into the quest for human genetic enhancement; Alan Lightman's reflections on how technology changes the experience of our humanness.
Keywords: Technology,Technological innovations; Social aspects,Social aspects